2013
DOI: 10.1103/physrevlett.111.037205
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Quasiparticles and Incoherent Photoemission Spectra inNa2IrO3

Abstract: We study two Kitaev-Heisenberg t-J-like models on a honeycomb lattice, focusing on the zigzag magnetic phase of Na(2)IrO(3), and investigate hole motion by exact diagonalization and variational methods. The spectral functions are quite distinct from those of cuprates and are dominated by large incoherent spectral weight at high energy, almost independent of the microscopic parameters-a universal and generic feature for zigzag magnetic correlations. We explain why quasiparticles at low energy are strongly suppr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…Hence, we determine the bound state by the divergent condition for Eq. (12). We find that one eigenvalue of Eq.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Hence, we determine the bound state by the divergent condition for Eq. (12). We find that one eigenvalue of Eq.…”
mentioning
confidence: 78%
“…For this reason, much attention has recently been paid to Ir oxides such as Sr 2 IrO 4 1-8 and Na 2 IrO 3 . [9][10][11][12] In particular, we focus on Sr 2 IrO 4 , which consists of two-dimensional IrO 2 layers showing structural similarity to the parent compound of high-T C cuprate La 2 CuO 4 , and exhibits a canted antiferromagnetic (AFM) order below 230 K. [1][2][3] The energy of the e g orbitals is estimated about 2 eV higher than that of the t 2g orbitals due to the large crystal field. Five 5d electrons are occupied per Ir atom, and one hole is sitting in the t 2g orbitals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence it was suggested that the numerous simplifications required by the SCBA are in fact too restrictive and a more resilient approach is needed to better understand the effective models of e g systems. Here we make such an attempt via the variational approximation (VA) [10][11][12][13], i.e., solving the equations of motion for the Green function. This method has previously been used by the authors to study a variety of interacting problems, among them an exactly solvable p-d system with FM order, which is a possible model for spin chains in cuprates [14].…”
Section: Introductionmentioning
confidence: 99%
“…This basis is usually very close to the relativistic J ef f =1/2 orbital. [5,16,20,23,24] Superexchange-based formalism is used to describe the zigzag-type AFM ordering. [14,25] The observed PM insulating state well above T N supports the Mott-type mechanism.…”
mentioning
confidence: 99%